Yogurt Consumption Behavior and Willingness to Pay for Biodegradable Packaging Yogurt in Hat Yai District, Songkhla Province - Chuchom, Tiyaporn; Kiatpathomchai, Sirirat; Thongrak, Sutonya (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2020)
The purposes of this study were to investigate the social and economic characteristics of the consumers, yogurt consumption behavior, and the willingness to pay (WTP) for biodegradable packaging yogurt in Hat Yai district, Songkhla province. Data were collected from 400 yogurt consumers. Data were analyzed by using descriptive statistics. In addition, Interval Data Method was applied to evaluate WTP. The results revealed that most of the consumers were female and an average age was 32 years old. The consumers (54.3%) obtained at least a Bachelor degree. Their personal income was 21,891 Baht/month on average. The consumers (35.5%) consumed yogurt due to nutrition and digestion benefits. The consumers spent 58.31 Baht for each purchase and 75.3% preferred to buy cup yogurt at convenience and grocery stores (82.5%). The consumers (94.7%) agreed that marketing promotion affect their decisions to buy cup yogurt, especially via TV and internet (42.7%). The consumers have moderate knowledge regarding biodegradable packaging, but have positive attitude towards biodegradable packaging. The results of WTP revealed that the consumers are willing to pay extra 4.81 Baht/cup for biodegradable packaging. (size 135 ml.) The extra WTP has positive relationship with yogurt expense for each purchase (p-value = 0.01) and attitude on biodegradable packaging (p-value = 0.05). Conversely, it has negative relationship with the cups of each purchase (p-value = 0.05).